Steady state visually evoked potential: Cortical frequency response in healthy subjects - Padilla, Gerardo Luis (2020)
A Brain Computer Interface (BCI) is an alternative communication system that replaces conventional pathways such as speech and movement. A BCI acquires signals from the brain (e. g., electroencephalogram, EEG) during the performance of cognitive tasks that reflects the user's desire or intention. In recent years, efforts have been made to optimize the information transfer speed of this alternative communication channel through systematic responses by the brain that do not depend or minimally depend on the user's emotional/cognitive state. For this reason, the steady-state visual evoked potentials (SSVEP) have taken a boom in research and implementation of BCI systems. This study aims to characterize the ability to evoke SSVEP at different stimulation frequencies. It is referred to herein as cortical frequency response.